2022
DOI: 10.1038/s41597-022-01654-2
|View full text |Cite
|
Sign up to set email alerts
|

RSDB: A rare skin disease database to link drugs with potential drug targets for rare skin diseases

Abstract: Rare skin diseases include more than 800 diseases affecting more than 6.8 million patients worldwide. However, only 100 drugs have been developed for treating rare skin diseases in the past 38 years. To investigate potential treatments through drug repurposing for rare skin diseases, it is necessary to have a well-organized database to link all known disease causes, mechanisms, and related information to accelerate the process. Drug repurposing provides less expensive and faster potential options to develop tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
3
0
3
Order By: Relevance
“…Compared to existing databases, such as Orphanet ( Weinreich et al 2008 ), NORD ( Putkowski 2010 ), RareDDB ( Gupta et al 2016 ), RSDB ( Kuo et al 2022 ), GARD ( Nguengang Wakap et al 2020 ), and eRAM ( Jia et al 2018 ), RDBridge encompasses all data categories found in other databases, while also providing a web server ( Supplementary Table S3 ). Moreover, RDBridge integrates medical image information and establishes connections with diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to existing databases, such as Orphanet ( Weinreich et al 2008 ), NORD ( Putkowski 2010 ), RareDDB ( Gupta et al 2016 ), RSDB ( Kuo et al 2022 ), GARD ( Nguengang Wakap et al 2020 ), and eRAM ( Jia et al 2018 ), RDBridge encompasses all data categories found in other databases, while also providing a web server ( Supplementary Table S3 ). Moreover, RDBridge integrates medical image information and establishes connections with diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Although a few manually curated databases have been established ( Putkowski 2010 , Weinreich et al 2008 ), and efforts have been made to clean and integrate these ( Gupta et al 2016 , Hoskins 2022 , Kuo et al 2022 ), a scarcity of knowledge remains ( Nguengang Wakap et al 2020 ) due to the low efficiency and timeliness of manual annotation. Gathering and exploring multiple data sources remains a time-consuming task that requires significant expertise, and a considerable amount of potential knowledge remains trapped within unstructured text ( Nadif and Role 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Repurposing established drugs is a way to quickly find more effective treatments, which can be used to stabilize pandemics or treat rare diseases. Such drug repurposing has been promoted extensively over the past few years, as it is a rapid drug development approach able to bring effective drugs to the market for a variety of indications [26,27]. The field of cosmeceuticals targeting the skin is no exception: skin appearance is essential for self-esteem and quality of life, and therefore skincare products represent a huge market.…”
Section: Discussionmentioning
confidence: 99%
“…Choroba jest genetycznie uwarunkowaną rzadką dermatozą skórną. Powstaje w wyniku upośledzenia w połączeniu warstw skóry właściwej i naskórka [1][2][3], na skutek czego zmniejszona jest wytrzymałość skóry na obciążenia mechaniczne [4,5]. Nawet najmniejszy ucisk lub otarcie skutkuje powstaniem ubytków skóry i niegojących się pęcherzy wypełnionych surowiczym płynem, które w następstwie z powodu kruchości tkanek mogą tworzyć rozległe rany i nadżerki [6][7][8].…”
Section: Pęcherzowe Oddzielanie Się Naskórkaunclassified
“…Częstym objawem u osób z EB jest świąd [3,21]. Poza dokuczliwością stanowi on niezwykle istotny czynnik protekcyjny do drapania skóry, co w konsekwencji prowadzi do powstawania kolejnych pęcherzy.…”
Section: Pęcherzowe Oddzielanie Się Naskórkaunclassified